INTER-RELATIONSHIPS AMONG SPEAKING ANXIETY, CONFIDENCE AND PERCEIVED ABILITY IN ENGLISH ORAL COMMUNICATION OF MALAYSIAN SCIENCE AND TECHNOLOGY UNDERGRADUATES - Badrasawi, Kamal J I; Sidik, Sakinah; Abu Kassim, Noor Lide; Zubairi, Ainol Madziah; Md Johar, Elia (Kulliyyah of Education, IIUM, 2020)
The use of English as a second language (ESL) in oral communication is crucial for science and technology undergraduates. However, studies have found that Malaysian undergraduates continue to struggle with low levels of English oral communication due to several factors such as speaking anxiety, low selfconfidence and low perceived ability in oral communication. There is still a need for further research to investigate the inter-relationships among these factors, and how they affect the English oral communication level among Malaysian science and technology undergraduates. Hence, this study aimed to identify the levels of English speaking anxiety, self-confidence and perceived ability in English oral communication, and find inter-relationships among the three factors. Three hundred (300) final year science and technology undergraduates were selected from three Malaysian public universities to complete a survey on factors affecting English oral communication. The Rasch Measurement modeling for polytomous data, descriptive statistics and Pearson correlation coefficient test were utilized to analyze the collected data. Overall, science and technology undergraduates showed moderate level of speaking anxiety, low self-confidence, and yet, high level of perceived ability in English oral communication. There are significant negative relationships between English speaking anxiety with self confidence and perceived ability in English oral communication. Recommendations are presented based on the research findings.